2015
DOI: 10.4103/0974-1208.165152
|View full text |Cite
|
Sign up to set email alerts
|

Empty follicle syndrome: Successful pregnancy following dual trigger

Abstract: Empty follicle syndrome (EFS) is an uncommon, but the frustrating complication of assisted reproductive technology with failure to obtain oocytes after an adequate ovarian response to stimulation. Most of the reported cases of EFS are drug-related problems which are actually avoidable and do not represent any potential pathology and that the risk of genuine EFS (GEFS) is much smaller than was once thought. Our case is the first report of a pregnancy obtained after management of GEFS with dual trigger in a gona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
1
7
0
3
Order By: Relevance
“…A similar case has been described by Deepika et al. ( 34 ), with two consecutive EFS cycles with adequate follicular development and hormonal levels, and an uneventful oocyte pick-up after the use of an hCG trigger. In a third attempt, using GnRH antagonist co-treatment, the dual trigger option was chosen.…”
Section: Empty Follicle Syndrome Following Hcg Triggersupporting
confidence: 69%
“…A similar case has been described by Deepika et al. ( 34 ), with two consecutive EFS cycles with adequate follicular development and hormonal levels, and an uneventful oocyte pick-up after the use of an hCG trigger. In a third attempt, using GnRH antagonist co-treatment, the dual trigger option was chosen.…”
Section: Empty Follicle Syndrome Following Hcg Triggersupporting
confidence: 69%
“…EFS can be classified as either "false" EFS or "genuine" EFS. The "false" EFS was due to the inappropriate timing and dosage of HCG administration (Isik & Vicdan, 2000;Meniru & Craft, 1997;Quintans, Donaldson, Blanco, & Pasqualini, 1998), after rescue protocols (Deepika, Rathore, Garg, & Rao, 2015;Hassan, Saleh, Khalil, Baghdady, & Ismaiel, 1998;Lok, Pritchard, & Lashen, 2003;Ndukwe et al, 1997;Penarrubia et al, 1999;Ubaldi et al, 1997), the oocytes can be harvested; whereas "genuine" EFS is termed as without oocytes nor cumulus-corona complexes being retrieved after improved protocols (La Sala et al, 1991;Onalan, Pabuccu, Onalan, Ceylaner, & Selam, 2003;Uygur, Alkan, & Batuoglu, 2003), which suggests underlying genetic defects. Previous studies identified homozygous mutations in the gene of LHCGR (MIM# 152790) in EFS (Yariz et al, 2011;Yuan et al, 2017).…”
mentioning
confidence: 99%
“…The use of an antagonist protocol may release the growing follicles from the strong suppressive effect of a GnRH agonist. Additionally, dual triggering with HCG and GnRH agonist was used, as suggested in a previous case report (Deepika et al ., 2015). Furthermore, measuring HCG level on the day of ovum pick up confirmed our diagnosis.…”
Section: Discussionmentioning
confidence: 99%